The Responsibility to Protect Doctrine (RtoP) in the Context of the Alleged Atrocity Crimes in the Occupied Palestinian Territories: The Relevance and Applicability - Sameh Eissa Abdelhalim Ismail; Hendun Abd. Rahman Shah (Penerbit Universiti Islam Selangor, 2026)
Indexed by (Tier 3)